Das Recht auf informationellen Systemschutz Plädoyer für einen Paradigmenwechsel im Datenschutzrecht - Pfaffinger, Monika (Nomos Verlagsgesellschaft mbH & Co. KG, 2022)
In this work, the call for a broader perspective in data protection law is deduced in three parts: the first, historical part shows that personal data processing has always been linked to information flows and society institutions, and not just to individual subjects. The second part exposes three structural hallmarks of the DPA. The third part addresses impact deficits of data protection law, the challenges raised by new technologies and commercialization, and the latest approaches to solving them. The author suggests a shift in paradigm: the future data protection law must be a law of systemic data protection, which includes the protection of individual rights.